Resting cardiac function in adolescent non-suicidal self-injury: the impact of borderline personality disorder symptoms and psychosocial functioning - Koenig, Julian; Gaber, Lena; Parzer, Peter; Resch, Franz; Kaess, Michael (Psychiatry research, 2017)
Vagally mediated heart rate variability (vmHRV) is reduced in borderline personality disorder (BPD). Non-suicidal self-injury (NSSI) is associated with comorbid psychopathology, in particular BPD. We aimed to examine differences in cardiac function (vmHRV and heart rate [HR]) comparing adolescents (12-17 years) engaging in NSSI (n=30) and healthy controls (n=30). Further, we aimed to determine clinical concomitants of cardiac function in patients with NSSI. Analyses showed no significant group differences on cardiac function. Controlling for a host of confounding variables resting state HR and vmHRV in adolescents with NSSI were significantly correlated with BPD symptoms and the current level of functioning.
Available online 21 December 2016
Gesehen am 31.10.2018